Rapamycin-Loaded Lipid Nanocapsules Induce Selective Inhibition of the mTORC1-Signaling Pathway in Glioblastoma Cells - Séhédic, Delphine; Roncali, Loris; Djoudi, Amel; Buchtova, Nela; Avril, Sylvie; Chérel, Michel; Boury, Frank; Lacoeuille, Franck; Hindré, François; Garcion, Emmanuel (Frontiers in Bioengineering and Biotechnology, 2021)
Inhibition of the PI3K/Akt/mTOR signaling pathway represents a potential issue for the treatment of cancer, including glioblastoma. As such, rapamycin that inhibits the mammalian target of rapamycin (mTOR), the downstream effector of this signaling pathway, is of great interest. However, clinical development of rapamycin has floundered due to the lack of a suitable formulation of delivery systems. In the present study, a novel method for the formulation of safe rapamycin nanocarriers is investigated. A phase inversion process was adapted to prepare lipid nanocapsules (LNCs) loaded with the lipophilic and temperature sensitive rapamycin. Rapamycin-loaded LNCs (LNC-rapa) are approx. 110 nm in diameter with a low polydispersity index (< 0.05) and the zeta potential of about -5 mV. The encapsulation efficiency, determined by spectrophotometry conjugated with filtration/exclusion, was found to be about 69% which represents 54 wt% of loading capacity. Western blot analysis showed that LNC-rapa do not act synergistically with X-ray beam radiation in U87MG glioblastoma model in vitro. Nevertheless, it demonstrated the selective inhibition of the phosphorylation of mTORC1 signaling pathway on Ser2448 at a concentration of 1 µM rapamycin in serum-free medium. Interestingly, cells cultivated in normoxia (21% O2) seem to be more sensitive to mTOR inhibition by rapamycin than those cultivated in hypoxia (0.4% O2). Finally, we also established that mTOR phosphorylation inhibition by LNC-rapa induced a negative feedback through the activation of Akt phosphorylation. This phenomenon was more noticeable after stabilization of HIF-1α in hypoxia.